Multiport bidirectional converter for solar fed hybrid electric vehicle using switched reluctance motor drive - Kollati, Sivaprasad; Gudey, Satish Kumar (International Journal of Applied Power Engineering (IJAPE), 2024)
For use in solar-assisted hybrid electric vehicle applications, a multiport bidirectional switched reluctance motor (SRM) drive is suggested in this research. Since the photovoltaic (PV) system's output voltage is low and insufficient to reach the necessary voltage level, a high gain KY converter is used to increase the PV output. The 8/6 SRM receives the steady converter output via the (n+1) diode (n+1) converter architecture with the help of the proportional integral (PI) controller. A PI controller regulates the SRM's speed. A bidirectional battery converter connects the battery, which is attached to the DC bus, to the extra power from the PV. A PI controller manages the bidirectional battery converter's operations. When necessary, the battery transfers the excess energy from the PV to the SRM drive. The outcomes demonstrate that, when examined using MATLAB simulation, the recommended methodology functions well.